The Relationship between Diabetes Mellitus with Senile Cataracts - Shaifullah, Muhammad; Fatmawati, Nur Khoma; Ismail, Sjarif (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
A cataract is any condition of cloudiness of the eye lens (lens opacity) caused by denaturation of lens proteins, lens hydration, or both. Senile cataract refers to cataracts suffered by patients aged > 50 years. Cataract is a multifactorial disease. About 90% of cataract incidence is related to age. Other factors such as radiation exposure, trauma, medicine, or the presence of systemic disorders are also involved in diabetes melitus. The study’s goal was to analyze the relationship between diabetes mellitus and the incidence of senile cataract. The research was carried out using an analytical observational method and utilized a case-control study approach with individual matching. The data was taken from the medical record installation at the Eye Clinic of SMEC Samarinda with a purposive sampling method. The sample in this study included patients with eye disorders or diseases.The patients with a cataract diagnosis were involved as the case group, while non-cataract patients as the control group. All patients were received treatment at the SMEC Samarinda Eye Clinic in the period January to December 2021 and already met the research sample criteria. The data then tested using the Chi-Square test with a significance value of p <0.05, which was considered significant. A total of 334 samples were obtained, consisting of 167 case samples and 167 control samples. The results indicated that there was a relationship between diabetes mellitus and senile cataract (p = 0.000) with an odds ratio (OR) value of 3.150. It can be concluded that diabetes mellitus had a relationship with the incidence of senile cataract, since patients with diabetes mellitus were 3.150 times more at risk of suffering senile cataracts than non-diabetics patients.